TEDDI: Radiotherapy delivery in deep inspiration for pediatric patients - A NOPHO feasibility study - Lundgaard, A; Hjalgrim, L; Rechner, L; Josipovic, M; Joergensen, M; Aznar, M; Berthelsen, A; Borgwardt, L; Johansen, C; Loft, A; Safwat, A; Vaalavirta, L; et al. (BioMed Central, 2018)
Background Radiotherapy (RT) delivered in deep inspiration breath-hold (DIBH) is a simple technique, in which changes in patient anatomy can significantly reduce the irradiation of the organs at risk (OARs) surrounding the treatment target. DIBH is routinely used in the treatment of some adult patients to diminish the risk of late effects; however, no formalized studies have addressed the potential benefit of DIBH in children. Methods/Design TEDDI is a multicenter, non-randomized, feasibility study. The study investigates the dosimetric benefit of RT delivered in DIBH compared to free breathing (FB) in pediatric patients. Also, the study aims to establish the compliance to DIBH and to determine the accuracy and reproducibility in a pediatric setting. Pediatric patients (aged 5–17 years) with a tumor in the mediastinum or upper abdomen with the possible need of RT will be included in the study. Written informed consent is obligatory. Prior to any treatment, patients will undergo a DIBH training session followed by a diagnostic PET/CT- or CT-staging scan in both DIBH and FB. If the patient proceeds to RT, a RT planning CT scan will be performed in both DIBH and FB and two separate treatment plans will be calculated. The superior treatment plan, i.e. equal target coverage and lowest overall dose to the OARs, will be chosen for treatment. Patient comfort will be assessed daily by questionnaires and by adherence to the respiratory management procedure. Discussion RT in DIBH is expected to diminish irradiation of the OARs surrounding the treatment target and thereby reduce the risk of late effects in childhood cancer survivors.